LEPROSY NEUROPATHY - Fahrani Yossa Prachika; Shahdevi Nandar Kurniawan (Journal of Pain, Headache and Vertigo, 2023)
Leprosy is a major cause of peripheral neuropathy in developing countries, affecting sensory, motor, and autonomic nerve function. Neuropathy complications can include sensory loss and muscle weakness. Impaired sensory nerve function is often the first symptom encountered in leprosy neuropathy. Early detection and treatment of neuropathy in leprosy are important to prevent disability.